The “internationalization” of first names: Gorani people in Belgrade and Germans in Vojvodina - Jadranka Đorđević-Crnobrnja (University of Belgrade, 2016)
The paper considers the social practice of giving and using first names among Gorani people in Belgrade and Germans in Vojvodina in the late 20th and the beginning of the 21st century. The first name, along with the surname represents the primary identification code, and it also often figures as a marker and symbol of ethnic and/or religious identity. This is known as the use of anthroponymy in the construction of the ethnic and religious identity of the individual. While the link between first names and ethnic and religious backgrounds may exist, it should not be the main means of identification. However, this occurs in practice. Due to this form of identification, people can experience various problems. Keeping this in mind, the paper considers the influence of outside (macro) factors on the choice and usage of first names among Gorani people in Belgrade and Germans in Vojvodina with the intent to establish and explain the reasons for the appearance of the “internationalization” of first names in these communities.